Magnetic Hysteresis and Barkausen Noise in Plastically Deformed Steel Sheets - Fausto Fiorillo; Michaela Küpferling; Carlo Appino (Metals, 2017)
The magnetic properties of steels are affected by plastic deformation, because the domain wall processes magnetoelastically interact with the dislocations and the residual stresses. The evolution of the magnetic hysteresis loop and its parameters with the type and degree of straining can thus provide a macroscopic signature of the underlying the mechanical and structural properties. Additional information can be achieved at a microscopic level through analysis of the Barkhausen noise, the signal generated by the stochastic flux variations associated with the discontinuous motion of the domain walls. Nondestructive methods for the structural evaluation of magnetic steels, devoted, in particular, to the investigation of work-hardening and state of internal stress following plastic straining, have therefore been developed in the literature, either through magnetic hysteresis or Barkhausen noise measurements. In this paper, we summarize significant results regarding the relationship between magnetic properties and plastic deformation in steel samples and the related experimental methods. Attention will be devoted, in particular, to the measurement and analysis of the Barkhausen noise spectral density and the way it relates to the macroscopic magnetic behavior and the structural properties.